LATE PREHISPANIC OCCUPATIONS IN THE CHILLON VALLEY: AN APPROACH FROM THE HUACA PRO - Raymondi Cárdenas, Antonio (2014)
This preliminary research results from prospecting and archaeological survey conducted in the valley under the Chillon. The central area is the left side and from the archaeological site Huaca Pro series Formal and Perceptive characters that allow an understanding of the social dynamics are analyzed. The settlement is analyzed within and interspace level, approaching proxemic sense understanding between nearby. All this through indicators such as siting, orientation, spatial configuration, materials, elements, etc., reflecting roles that were acquired by the Huaca Pro for late pre-Hispanic period.